ANALISIS TINDAK TUTUR ILOKUSI PADA PROGRAM MUSTANG PLAYGROUND WITH NO NA: KAJIAN PRAGMATIK JOHN SEARLE - Della Eka Putri; Sumarti Sumarti; Nurlaksana Eko Rusminto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze illocutionary speech acts in the program “Mustang Playground with No Na” on the Mustang 88 FM YouTube channel based on John Searle’s speech act theory. This research employs a qualitative approach with a descriptive method. The data were collected using observation and note-taking techniques, along with transcription of utterances between the host and No Na members in question-and-answer segments and game sessions. The data were analyzed by classifying utterances into types of illocutionary acts, namely assertive, directive, expressive, commissive, and declarative. The findings show that assertive and directive speech acts are the most dominant, indicating that the interaction in the program is mainly characterized by information sharing, experiences, opinions, and the organization of the show and games. Expressive speech acts appear less frequently but function to build emotional atmosphere, while commissive acts are very limited and declarative acts are not found because the program is informal and does not involve institutional authority. This study lies in the analysis of illocutionary speech acts in a digital YouTube entertainment program that combines talk show elements and interactive games as a medium for music promotion. This study demonstrates that digital entertainment is a dynamic space for pragmatic communication